A case series: Association of anaphylaxis with a significant decrease in platelet levels and possible secondary risk of thrombosis. Issue 3 (26th April 2018) - Peppers, Brian P.; Vatsayan, Anant; Dalal, Jignesh; Bonfield, Tracey; Tcheurekdjian, Haig; Hostoffer, Robert
Abstract: Introduction: Anaphylaxis is a life threatening systemic inflammatory process that share mediators involved in the coagulation cascade. Platelet activating factor, known to increase platelet aggregation, has also been implicated as an important mediator of anaphylaxis. Although other inflammatory reactions are associated with an increased risk of thrombosis, anaphylaxis is currently not reported as one of them. Furthermore the role platelets may have in the perianaphylaxis period is not well understood. We here in present a retrospective case series of three patients that had platelet aberrations suggestive of PAF involvement and clinically significant thrombosis in close relationship with anaphylaxis. Objective: To investigate platelet response before and after anaphylaxis and indirect observation evidence of platelet activating factors involvement with possible increased risk of thrombosis. Methods: A retrospective investigation into medical records including medication administrations times, laboratory, and radiology results. Platelet levels pre‐ and post‐ anaphylaxis were statistically analyzed. Results: Case 1, a 44 year old man had an anaphylactic reaction shortly after envenomation and subsequently suffered an acute infarction with thrombus in a cerebral artery. Case 2 is a 49 year old man with idiopathic anaphylaxis who developed a deep vein thrombosis after a protracted anaphylaxis event. Case 3 involved an 18 year old female with acute myeloid leukemia was found to have a thrombus in the celiac trunk following anaphylaxis. A paired two‐tailed Wilcoxon test on the subjects pre and post anaphylactic platelet levels resulted in a overall P < 0.0001. Conclusions and Clinical Relevance: These three cases illustrate the potential role platelets may have in anaphylaxis and possible increased secondary risk for the development of thrombosis. Larger studies are required to determine incidence and risk factors for blood clots following anaphylaxis in order to provide management or screening recommendations. Abstract : Anaphylaxis is a life threatening systemic inflammatory process that share mediators involved in the coagulation cascade. Platelet activating factor, known to increase platelet aggregation, has also been implicated as an important mediator of anaphylaxis. Although other inflammatory reactions are associated with an increased risk of thrombosis, anaphylaxis is currently not reported as one of them. Furthermore the role platelets may have in the perianaphylaxis period is not well understood. We here in present a retrospective case series of three patients that had platelet aberrations suggestive of PAF involvement and clinically significant thrombosis in close relationship with anaphylaxis.